Formation of zirconia nanoparticles on silica matrix - Borisenko, N. V.; Gun'ko, V. N.; Sulim, I. Ya.; Dyachenko, A. G.; Leboda, R.; Skubiszewska-Zieba, Ya. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2006)
IR-spectroscopy, nitrogen adsorption-desorption, and XRD were used to investigate the chemosorption of ZrCl4 and Zr(acac)4 and formation of ZrO2 nanoparticles on silica surface. The structure was determined and hydrolytic and thermal properties of grafted groups were investigated. Highly disperse ZrO2/SiO2 (4,2 – 21,8 wt % ZrO2) samples were synthesized by a CVD method (chemical vapor deposition) of ZrCl4 on the surface of silicas (A-300 and Si-60) and by a subsequent hydrolysis and dehydration. It was found that silica surface stabilizes the tetragonal zirconia. Amorphous ZrO2 nanoparticles were prepared due to chemosorption of Zr(acac)4 (from CCl4 solution) on fumed silica and thermal tretment.